IMPLEMENTASI KURIKULUM MERDEKA BELAJAR KELAS XI DI SMA NEGERI 3 KENDARI PADA MATA PELAJARAN KIMIA - Ingki; Aceng Haetami; Dahlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum from the planning, execution, and evaluation stages, as well as to identify the constraints faced by eleventh-grade chemistry teachers at SMA Negeri 3 Kendari. The research method used was a descriptive qualitative approach, with data collected through questionnaires, interviews, observations, and documentation. The results indicated that the implementation of the Merdeka Curriculum fell into the "Excellent" category, with the planning stage reaching 85.92%, the execution stage at 88.57%, and the evaluation stage achieving 93.33%. The constraints encountered by teachers were relatively low ("Very Low Difficulty" at 81.77%), with the primary challenges being adapting learning strategies to diverse student characteristics and managing project-based learning. Overall, the implementation of the Merdeka Curriculum in chemistry subjects at this school has run effectively, driven by adequate facilities and continuous professional training provided by the school.